2005
DOI: 10.1111/j.1365-2494.2005.00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of herbage regrowth and water‐soluble carbohydrate concentration of ryegrass species to defoliation practices when grown in a Mediterranean environment

Abstract: Three experiments were conducted to determine the association between leaf number per tiller at defoliation, water-soluble carbohydrate (WSC) concentration and herbage mass of juvenile ryegrass plants when grown in a Mediterranean environment. Seedlings of ryegrass were grown in nursery pots arranged side-byside and located outside in the open-air to simulate a mini-sward in Experiments 1 and 2, and a mixture of annual ryegrass and subterranean clover (Trifolium subterraneum L.) was grown in a small plot field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 15 publications
4
7
0
3
Order By: Relevance
“…These results are consistent with those observed by Hume (1991) and Callow et al (2005) who found that frequent defoliation reduced herbage mass and leaf size in various grass species. These results are consistent with those observed by Hume (1991) and Callow et al (2005) who found that frequent defoliation reduced herbage mass and leaf size in various grass species.…”
Section: Herbage Mass Accumulation and Growth Dynamicssupporting
confidence: 93%
“…These results are consistent with those observed by Hume (1991) and Callow et al (2005) who found that frequent defoliation reduced herbage mass and leaf size in various grass species. These results are consistent with those observed by Hume (1991) and Callow et al (2005) who found that frequent defoliation reduced herbage mass and leaf size in various grass species.…”
Section: Herbage Mass Accumulation and Growth Dynamicssupporting
confidence: 93%
“…() using perennial ryegrass ( Lolium ryegrass L.), Callow et al. () annual ryegrass ( Lolium rigidum Gaud.) and Italian ryegrass ( Lolium multiflorum Lam.…”
Section: Discussionmentioning
confidence: 99%
“…Defoliation treatments were imposed when greater than 50% of 10 randomly selected tillers attained the set number of fully expanded leaves, that is, 2, 3 and 4 leaves/tiller (Callow, Michell, Baker, Cocks, & Hough, ; Fulkerson & Slack, ; Turner, Donaghy, Lane, & Rawnsley, ). The expansion of each new leaf was termed “1‐leaf stage” and thus the respective treatments were referred to as 2‐leaf, 3‐leaf and 4‐leaf stages.…”
Section: Methodsmentioning
confidence: 99%
“…(1997), who also used a leaf‐labelling technique. Similar to the present study, Callow et al. (2005) found in pot and small plot experiments that the root biomass of perennial ryegrass constituted a considerable proportion of the total plant biomass with shoot:root ratios estimated to be in the range of 0·8–1·2.…”
Section: Discussionmentioning
confidence: 99%